The representation of ideal city in property advertisements in Indonesia: Critical discourse analysis on Meikarta and Podomoro Golf View advertisements - Adityarini K.; Riswani; Roni Kurniawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
In 2016 and 2017, Meikarta and Podomoro Golf View (PGV) were offering the Ideal City for the consumers in Indonesia. These projects were promoted by audiovisual advertisements. Therefore, the research aimed to compare the representation of ideal city in Meikarta and PGV advertisements. The research used a qualitative design in conducting the study. The data were the Meikarta audiovisual advertisement “Aku ingin pindah ke Meikarta” and the PGV audiovisual advertisement in 2017. To find the objective of the research, the researcher used Critical Discourse Analysis by Fairclough (1996) in emphasizing on language and power inequality. Fairclough (1996) introduced the model of discourse analysis, such as: text, interaction, and context. Moreover, to identify whether were or not the relationship between language; ideology; and power, the researcher applied three dimensions by Fairclough in analyzing the data, namely: Description, Interpretation, and Explanation. Then, the research figured out that both of advertisements had concepts to attract the consumers to buy the products by demonstrating the concepts of ideal city, such as: no traffic jam, modern transportation system, health center, good weather, greenery, and easy access. Besides that, the researcher found out on how ideology and power tightly displayed in the advertisements.